Frigitilla gen. nov., a new genus of Amazonian Mutillidae (Hymenoptera) - Bartholomay, Pedro R.; Williams, Kevin A.; Luz, David R.; Morato, Elder F. (Zootaxa, 2015)
Mutilla frigidula Cresson, 1902 was transferred to Tobantilla by Williams et al. (2011), based on morphological similarities with females of that genus. Discovery of the male of this species indicated significant morphological differences from Tobantilla. We therefore erect the genus, Frigitilla gen. nov., for Mutilla frigidula. Herein, we describe the male of F. frigidula (Cresson, 1902), comb. nov., associate it with its host (Trypoxylon spp.), and discuss its relations to other mutillid genera. The impact of collecting method and specimen age on the integumental coloration of specimens is discussed, emphasizing the need to diagnose species on consistent structural features rather than differences in color pattern.